Technical and Economical Analysis of a Solar Power System Supplying a Residential Consumer. (2016) - Ronay, Karoly; Dumitru, Cristian Dragos
Abstract: This paper presents the design and technical-economic analysis of a solar power system for a residential consumer. One of the main objectives is to design an optimal power system based on solar energy resources for a chosen power consumer. The power consumer represents the starting point of the analysis, contains both AC and DC users and, before the design process, the type and variety of the electrical loads has to be well known. This aspect is important in designing the power system topology, to be more economical and compatible with all the power consumers. The aim of the paper is to present the design and functionality of the solar power system, determining the energy production and consumption for the proposed system. Also an important aspect of the paper is the analysis of the system from technical and economical point of view, to present the overall results. The approach is to study the power system, starting from the solar radiation data, which is a known parameter, to calculate the system equipment sizes and power losses and to find an optimal energy production/consumption ratio. To fulfill this task the proposed research methodology is to configure the optimal system structure (solar panels, chargers, inverters), to gather information about the value of the equipment and to deduct the payback period of the system, under normal functioning conditions.